Detecting early kidney injury due to host–virus interaction response in treatment-naive CHB—a pilot study - Gandhi, Puneet; Peter, Kavita; Varshney, Subodh; Atlani, Mahendra Kumar; Maudar, Kewal Krishan (Frontiers in Cellular and Infection Microbiology, 2025)
PurposeClinical evidence suggests that patients with chronic hepatitis B (CHB) have an increased risk of renal impairment due to inflammation induced by virus–host interaction. We aimed to evaluate and validate a set of protein biomarkers singularly and in combination for the early detection of subclinical kidney injury in patients with CHB naive to antiretroviral therapy.MethodsThis work is part of a prospective cross-sectional study for which 69 HBsAg-positive, treatment-naive patients with CHB with an equal number of age-matched healthy volunteers were considered. At diagnosis, serum creatinine (sCr), urea, alanine transaminase, aspartate transaminase, serum cystatin-C (sCys-C), serum neutrophil gelatinase-associated lipocalin (sNGAL), serum Fetuin-A (sFet-A), urinary interleukin-18 binding protein (uIL-18BP), and urinary kidney injury molecule-1 (uKIM-1) levels were determined.ResultsThere was a significant elevation in the concentrations of three proteins in our CHB cohort (sCys-C, sNGAL, and uIL-18BP; p < 0.0001) while sFet-A was down-regulated (p<0.01) as compared to the control group. A receiver operating characteristic curve analysis revealed an Area under the curve of 0.935 for sCys-C and 0.811 for sNGAL, which improved to 0.984 when all four indicators were combined in a panel to discriminate the onset of renal injury incited by inflammatory response in CHB with 97.1% sensitivity at 91.3% specificity. Additionally, only sCys-C and sNGAL differed significantly among the phases of CHB infection (p<0.05). ConclusionsThis novel noninvasive diagnostic screen is expedient in detecting inflammation and early kidney injury before a rise in sCr and can aid in predicting renal outcomes in patients with CHB.